KRIMINALISASI NARKOBA: DITINJAU DARI TEORI LABELING PADA KASUS PELAKU PERDAGANGAN NARKOBA DI LAPAS PEREMPUAN - Ciek Julyati Hisyam; Alya Alifah Nuraini; Fahria Izzatul Islamiya; Koputri Sipah Fauziah; Sri Yulia Vevita Ravelia (Yayasan Literasi Sains Indonesia, 2023)
Drug trafficking throughout Indonesia has been very worrying for the younger generation, even leading to criminal acts that cause victims and do not cause victims. It is also influenced by the labeling of drug users and dealers by society. Labeling the perpetrators can have a significant impact. This is because people who violate norms are seen as deviants, because their behavior is not in accordance with the norms and rules of society. The purpose of the research is to explain the dangers of labeling drug users and dealers by society. This research will explain the definition of drug criminalization, drug criminalization in terms of labelling theory, the form and process of labelling, the factors that influence a person to become a drug offender, and the impact of drug criminalization. The data analysis used in the research was carried out with a descriptive method using a qualitative approach, collecting data with in-depth interviews with informants and key informants in the prison. The sanction system for drug addicts in addition to including criminal sanctions, also includes rehabilitation measures to eliminate the effects of drug dependence. The results of the study explain the dangers of labeling from society to drug users and dealers.